The shaping of adolescent physical activity habitus: The role of family sports culture - Haoyuan Zheng; Zubing Xiang; Wenli Yang; Haojun Xi (PLoS ONE, 2025)
Based on Bourdieu’s habitus theory, this study revealed the connotation, function, and shaping mechanism of physical activity habitus. Utilizing a stratified random cluster sampling survey conducted across 16 public undergraduate universities in Chongqing, China, the data were quantitatively analyzed using factor analysis and OLS regression analysis models to explore the impact of family sports culture on the formation of adolescent physical activity habitus in primary school, middle school, and high school. The study constructed two main dimensions of adolescent physical activity habitus: self-report physical behavioral capacity and physical behavioral inclination. Further research indicates that family sports culture may maintain a certain correlation with the two dimensions of adolescents’ physical activity habits throughout their entire educational trajectory. Moreover, it is noteworthy that factors such as family economic status, paternal education level, gender, and urban-rural disparities appear to demonstrate weaker associations with adolescents’ physical activity habits when compared to the influence of family sports culture. In conclusion, this study suggests that family sports culture during the primary school stage may represent a potentially critical factor in shaping adolescents’ physical activity habits. Therefore, it is imperative for all sectors of society to pay more attention to the construction of family sports culture.